Optical solitons for cascaded system: Jacobi elliptic functions - Tchier, Fairouz; Aslan, Ebru Cavlak; İnç, Mustafa (Taylor & Francis Ltd, 2016)
In this work, the coupled NLSE is studied that appears in a cascased system. Exact solutions of this coupled system acquire by using Jacobi elliptic functions. The presented system will be studied with two forms of nonlinearity. The forms are kerr law and power law. Dark, bright, singular solitons and Jacobi elliptic solutions will be acquired. We present constraint conditions for the existence of obtained solitons. Our obtained solitons will be controlled by changing the diffraction coefficients.
Keywords: CS; Jacobi elliptic functions; integrability; optical solitons